2013
DOI: 10.1177/0163443713483654
|View full text |Cite
|
Sign up to set email alerts
|

Pakistani journalism: at the crossroads of Muslim identity, national priorities and journalistic culture

Abstract: A loosening of controls on the Pakistani media in recent years has meant the influence of Pakistani journalists is increasingly being felt in country’s tumultuous internal politics and its relations with the West. That has sparked a backlash, which has made Pakistan among the most dangerous places in the world for journalists. Given the country’s key strategic role, both in terms of South Asian regional geo-politics and in the broader global struggle against radical Islamist militancy, it is important to bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In addition, a growing number of studies looked specifically at journalists' roles beyond the Western world. In a series of surveys, Pintak (; Pintak & Nazir, ), for instance, studied journalists in the Arab and Islamic world, finding them to serve their audiences in the capacity of an agent of change. Other studies have identified journalistic traits that correspond to the idea of “development journalism” in countries as diverse as Bangladesh, Indonesia, Nepal, and Nigeria (Edeani, ; Ramaprasad & Kelly, ; Ramaprasad & Rahman, ; Romano, ).…”
Section: Journalistic Roles In the Literaturementioning
confidence: 99%
“…In addition, a growing number of studies looked specifically at journalists' roles beyond the Western world. In a series of surveys, Pintak (; Pintak & Nazir, ), for instance, studied journalists in the Arab and Islamic world, finding them to serve their audiences in the capacity of an agent of change. Other studies have identified journalistic traits that correspond to the idea of “development journalism” in countries as diverse as Bangladesh, Indonesia, Nepal, and Nigeria (Edeani, ; Ramaprasad & Kelly, ; Ramaprasad & Rahman, ; Romano, ).…”
Section: Journalistic Roles In the Literaturementioning
confidence: 99%
“…A growing number of studies specifically look at journalists' roles beyond the western world. In a series of surveys, Pintak (2014;Pintak and Nazir 2013), for instance, found journalists in the Arab and Islamic world to serve their audiences in the capacity of an agent of change. Other studies identified journalistic traits that correspond to the idea of "development journalism" in parts of Asia and Africa (Edeani 1993;Ramaprasad and Kelly 2003;Ramaprasad and Rahman 2006;Romano 2003).…”
Section: Journalistic Roles In the Literaturementioning
confidence: 99%
“…The conditions under which journalists work in these countries clearly influence the way they reflect on journalism's contribution to society. Pintak (2014;Pintak and Nazir 2013) found journalists in the Muslim world act as "agents of change" in their respective communities. Such a perception may be driven by the particular political situation in these countries as well as by socio-cultural values.…”
Section: Journalistic Roles In Muslim-majority Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, Weaver and colleagues (Weaver and Wilhoit 1986;Weaver and Wu 1998;Weaver et al 4 CELESTE GONZÁLEZ DE BUSTAMANTE AND JEANNINE E. RELLY 2007; Weaver and Willnat 2012) have studied US journalistic values and role perceptions as they have evolved and others have subsequently studied professionalism around the world and in the region (Herscovitz 2004;Hughes 2006;Mellado et al 2012;Pintak andGinges 2008, 2009;Pintak and Nazir 2013) using modified models. However, in reflecting on studies of journalists in 31 countries and territories from around the world, Weaver and Willnat (2012, 544) concluded there are many differences across countries in the profession and "the patterns of similarities and differences are not neatly classifiable along some of the more common political or cultural dimensions.…”
Section: Professionalism In the Global Southmentioning
confidence: 99%